Self-Assembled Near-Infrared Dye Nanoparticles as a Selective Protein Sensor by Activation of a Dormant Fluorophore - Anees, Palapuravan; Sreejith, Sivaramapanicker; Ajayaghosh, Ayyappanpillai (Journal of the American Chemical Society, 2014)
Design of selective sensors for a specific analyte in blood serum, which contains a large number of proteins, small molecules, and ions, is important in clinical diagnostics. While metal and polymeric nanoparticle conjugates have been used as sensors, small molecular assemblies have rarely been exploited for the selective sensing of a protein in blood serum. Herein we demonstrate how a nonspecific small molecular fluorescent dye can be empowered to form a selective protein sensor as illustrated with a thiol-sensitive near-IR squaraine (Sq) dye (λabs= 670 nm, λem= 700 nm). The dye self-assembles to form nonfluorescent nanoparticles (D h = 200 nm) which selectively respond to human serum albumin (HSA) in the presence of other thiol-containing molecules and proteins by triggering a green fluorescence. This selective response of the dye nanoparticles allowed detection and quantification of HSA in blood serum with a sensitivity limit of 3 nM. Notably, the Sq dye in solution state is nonselective and responds to any thiol-containing proteins and small molecules. The sensing mechanism involves HSA specific controlled disassembly of the Sq nanoparticles to the molecular dye by a noncovalent binding process and its subsequent reaction with the thiol moiety of the protein, triggering the green emission of a dormant fluorophore present in the dye. This study demonstrates the power of a self-assembled small molecular fluorophore for protein sensing and is a simple chemical tool for the clinical diagnosis of blood serum.